A Geoprocessing Approach Using Poi Visibility Index for Identifying Potential Routes in Designing Sustainable Tourism Development: The Case Study of Singkawang, Indonesia - Purnomo, Yudi; Wulandari, Agustiah (JURNAL GEOGRAFI, 2025)
Regional planning and urban design are essential in developing a region or city. Point of Interest (POI) data in area planning can significantly influence resident perceptions and behaviors and shape investment decisions and development strategies in tourist areas. This study focuses on Singkawang City, a prominent coastal tourist destination on the island of Kalimantan, Indonesia. Singkawang features a historical spatial layout but faces numerous contemporary challenges. The research aims to identify potential efficient tourist routes using geographic analysis based on the POI visibility index. The research has practical benefits, including promoting tourism development, supporting local economic growth, optimizing land use, and enhancing urban user-friendliness. The study employs data on road networks, buildings, and tourist attraction points. The analysis identifies the nodes (POIs and intersections) that concentrate the most efficient routes in the study area, actively connecting tourist attractions in the city center. These routes demonstrate greater importance than those connecting natural attractions in the city's peripheral areas. User visitation levels and the visibility of POIs influence the city's morphological movement patterns. The findings highlight the strategic role of POI-based geographic analysis in improving urban connectivity and guiding regional planning efforts, offering valuable insights for addressing urban challenges and advancing sustainable, tourism-focused urban development.